O -Iodoxybenzoic Acid (IBX)-Iodine Mediated One-Pot Deacylative Sulfonylation of 1,3-Dicarbonyl Compounds: A Synthesis of β-Carbonyl Sulfones - Praewpan Katrun (2018)
© Georg Thieme Verlag Stuttgart · New York-Synthesis 2017. A combination of o-iodoxybenzoic acid (IBX) and a catalytic amount of iodine is found to promote a facile one-pot deacylative sulfonylation reaction of 1,3-dicarbonyl compounds with sodium sulfinates to yield β-carbonyl sulfones. The present method provides the target products bearing a wide variety of functional groups in one step and in good yields.